Cytotoxic and Antimicrobial activity of Diketopiperazines from Unidentified Marine-Derived Fungus - Maarisit, Wilmar (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Kristen Indonesia Tomohon, 2023)
Two new diketopiperizines 1 and 2 were isolated together with a known diketopiperazine cis-bis(methylthio)-silvatine (3) and a known 5a,8a-epidoxy-(22E,24R)-ergosta-6,22-dien-3b-ol(ergosterol peroxide) (4) from a marine-derived fungus. The structures of 1-4 were elucidated by 1D and 2D NMR analyses. Cytotoxicity of the isolated compounds against human colorectal cancer cell lines (HCT116) and their antibacterial and antifungal activities were evaluated.